Sliding mode control of a two degrees of freedom helicopter system - Oyman, Hilmi Artun. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2012., 2012)
In this thesis, one of the robust control methodologies, namely Sliding Mode Control (SMC) is applied to Quanser's Two Degrees of Freedom Helicopter System (2-DOFHS) and the performance of this approach is compared with the performances of other control methods such as Full State Feedback Control (FSFC) via Linear Quadratic Regulator (LQR) and Feedback Linearization (FL) with Pole Placement. Firstly, the mathematical model given by the manufacturer is investigated. Various parameters such as torque and friction constants are calibrated by trial and error. The mass of the system is assumed to be uncertain yet is bounded between the nominal mass and the mass with the maximum additional load. The nonlinear Multi-Input-Multi-Output (MIMO) sliding mode controller is designed in such a way that the uncertainties are taken into consideration. Control input is interpolated in a constant boundary layer to reduce the chattering problem. Finally, SMC is observed to give better results than the other approaches.
Keywords: Helicopters -- Control systems.